Evaluation of sarcopenia biomarkers in older patients undergoing major surgery for digestive cancer. SAXO prospective cohort study. Issue 1 (January 2023) - Gagnat, Guillaume; Hobeika, Christian; Modzelewski, Romain; Collet, Celine Savoye; Di Fiore, Frederic; Druesne, Laurent; Tuech, Jean Jacques; Schwarz, Lilian
Abstract: Background: The aim of the study was to prospectively evaluate different biomarkers to identify the most reliable for anticipating complications after major abdominal surgery for digestive cancer in older patients and compare their performance to the existing definition and screening algorithm of sarcopenia from EWGSOP. Methods: Ninety-five consecutive patients aged over 65 years who underwent elective surgery for digestive cancer were prospectively included in the SAXO study. Sarcopenia was defined according to EWGSOP criteria (four level from no sarcopenia to severe sarcopenia). Strength and physical performance were evaluated with the handgrip test (HGT) and gait speed test (GST), respectively. CT scan analysis was used to calculate the skeletal muscle index (SMI), intermuscular adipose tissue (IMAT), visceral adipose tissue (VAT), and subcutaneous adipose tissue (SAT). Measures were adjusted to body mass index (BMI). Complication grading was performed using the Clavien‒Dindo classification. A doubly robust estimator with multivariable regression was used to limit bias. Results: Sixteen patients presented with sarcopenia. Adjusted to BMI, sarcopenic patients had an increased IMAT BMI (0.35 vs. 0.22; p = 0.003) and increased VAT BMI (7.85 vs. 6.13; p = 0.048). In multivariable analysis, IMAT was an independent risk factor for minor and severe complications (OR = 1.298; 95% CI [1.031: 1.635] p  =  0.027 ), while an increased SAT area was a protective factor (OR = 0.982; 95% CI [0.969: 0.995] p  =  0.007 ). Twenty-two patients were obese (BMI ≥30 kg/m 2 ). While no association was observed between obesity and sarcopenia (according to EWGSOP definition), obese patients had increased IMAT BMI (0.31 vs. 0.23; p = 0.010) and VAT BMI (8.40 vs. 6.49; p = 0.019). The combination of SAT, VAT and IMAT performed well to anticipate severe complication (AUC = 0.759) while AUC of EWGSOP 2010 and 2019 algorithm were 0.660 and 0.519, respectively. Discussion: Non-invasive and imaging related measures of IMAT, SAT and VAT seems to be valuable tools to refine risk-assessment of older patients in surgery and specially to detect myosteatosis in obese ones.